Activation of Astroglial Calcium Signaling by Endogenous Metabolites Succinate and Gamma-Hydroxybutyrate in the Nucleus Accumbens - Molnár, Tünde; Héja, László; Emri, Zsuzsa; Simon, Ágnes; Nyitrai, Gabriella; Pál, Ildikó; Kardos, Julianna (Frontiers in Neuroenergetics, 2011)
Accumulating evidence suggests that different energy metabolites play a role not only in neuronal but also in glial signalling. Recently, astroglial Ca2+ transients evoked by the major citric acid cycle metabolite succinate (SUC) and gamma-hydroxybutyrate (GHB) that enters the citric acid cycle via SUC have been described in the brain reward area, the nucleus accumbens (NAc). Cells responding to SUC by Ca2+ transient constitute a subset of ATP-responsive astrocytes that are activated in a neuron-independent way. In this study we show that GHB-evoked Ca2+ transients were also found to constitute a subset of ATP-responsive astrocytes in the NAc. Repetitive Ca2+ dynamics evoked by GHB suggested that Ca2+ was released from internal stores. Similarly to SUC, the GHB-response was also characterized by an effective concentration of 50 µM. We observed that the number of ATP-responsive cells decreased with increasing concentration of either SUC or GHB. Moreover, the concentration dependence of the number of ATP-responsive cells were highly identical as a function of both [SUC] and [GHB], suggesting a mutual receptor for SUC and GHB, therefore implying the existence of a distinct GHB-recognizing astroglial SUC receptor in the brain. The SUC-evoked Ca2+ signal remained in mice lacking GABAB receptor type 1 subunit in the presence and absence of the N-Methyl-D-Aspartate (NMDA) receptor antagonist (2R)-amino-5-phosphonovaleric acid (APV), indicating action mechanisms independent of the GABAB or NMDA receptor subtypes. By molecular docking calculations we found that residues R99, H103, R252 and R281 of the binding crevice of the kidney SUC-responsive membrane receptor SUCNR1 (GPCR91) also predict interaction with GHB, further implying similar GHB and SUC action mechanisms. We conclude that the astroglial action of SUC and GHB may represent a link between brain energy states and Ca2+ signalling in astrocytic networks.